KINERJA RUAS JALAN CUT NYAK DIEN TERHADAP LEBAR PERKERASAAN JALAN - Syafrizal Syafrizal; Muhammad Idham (Racic : Rab Construction Research, 2023)
The cut nyak dien road in the city of Dumai is a provincial road that is often passed by CPO heavy transport vehicles and public transportation, On this road, traffic jams often occur due to disruption of CPO transport vehicles, where passing trucks cannot go because the roads are close to community areas, so trucks slow down, this affects the flow of traffic and the performance of these roads. For this reason, it is necessary to conduct studies related to the performance of road sections, so that problems that exist in the field can be controlled. The method used to analyze the performance of roads is using PKJI 2014. After the survey results were obtained and the analysis was carried out, the road capacity value was obtained, which was 2404 hours/hour and the highest exsisiting Degree of Saturation was obtained at 0.65, for DJ 5 and 10 years to come, it is known that the highest DJ is 0.77 and 1.03 so that it can be concluded that the s ervice level of the cut nyak dien road in the existing conditions is C indicating a stable flow, but the speed of the vehicle is controlled. Kata kunci : Performance, Road Segment, Speed, LOS